Beyond the ice: decoding Lake Mertzbakher’s response to global climate shifts - Zhang, Xin; Tang, Zhen; Zhou, Yan; Zhu, Jie; Sun, Gaohu; Huang, Chaowei (Frontiers in Environmental Science, 2024)
This study addresses the critical problem of understanding the changing dynamics of glacier meltwater in Lake Mertzbakher, a challenge heightened by ongoing global climate change. Employing the innovative method of the Google Earth Engine (GEE) platform, this research meticulously extracted surface water data at 60 time points during the years 2000, 2005, 2010, 2015, and 2021. This approach represents a significant advancement over previous methods by offering more frequent and precise data analysis. We incorporated meteorological factors such as temperature and precipitation to assess their influence on the monthly changes in the glacier lake area. Our findings indicate a pronounced outburst in July, leading to a substantial decrease in the lake's area, which reaches its lowest in September. Through detailed partial regression analysis, we established a hierarchy of meteorological influences on the lake's area, identifying minimum temperature (r=0.245), mean temperature (r=-0.239), precipitation (r=0.228), radiation (r=0.154), and maximum temperature (r=0.128) as key factors. Additionally, our use of a structural equation model unveiled the most impactful elements, with mean temperature (r=-3.320), minimum temperature (r=2.870), radiation (r=0.480), and precipitation (r=0.470) leading the effects. These 2 insights mark a substantial contribution to our understanding of glacier lake dynamics, offering crucial data for predicting and managing glacier lake floods. This study's novel methodology and comprehensive analysis underscore its significance in enhancing disaster prevention and preparedness strategies amidst the challenges of global climate change.